An intraocular lens and a method of manufacturing and using the same

CN121868574BActive Publication Date: 2026-10-09SOUTH CHINA NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610295353.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-11
Publication Date
2026-10-09
Estimated Expiration
2046-03-11

AI Technical Summary

Technical Problem

[0004]然而,现有技术中广泛使用的crySof SN60WF型号人工晶状体在闪辉加速实验中的表现较差,经加速后晶体内的微空泡密度较大,这些微泡在临床上会对患者视觉质量造成干扰,影响术后视觉体验和满意度

Benefits of technology

1)本发明提供的人工晶状体,交联密度与材料韧性间的平衡较好,加速老化后微空泡密度较现有产品(AcrySof IQ SN60WF)显著降低,有效抑制了闪辉现象,能够更好地保持长久的清晰度与视觉质量;该人工晶状体的热稳定性高,起始分解温度可达295℃,便于高温灭菌及后续加工;临床应用中,该人工晶状体可减少眩光、光晕等视觉干扰,降低二次手术风险,适用于白内障及高度近视等屈光不正患者的长期植入,可为患者提供更安全、持久的视觉质量保障;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and discloses an artificial lens as well as a preparation method and application thereof. The artificial lens comprises the following preparation raw materials: 2-phenylethyl acrylate, 2-methylstyrene acrylate, a crosslinking agent and an initiator. The artificial lens provided by the application has a good balance between crosslinking density and material toughness, the micro-bubble density of the artificial lens is significantly reduced after accelerated aging compared with existing products, the flash phenomenon is effectively inhibited, the long-term clarity and visual quality can be better maintained, the artificial lens has high thermal stability, the initial decomposition temperature can reach 295 DEG C, high-temperature sterilization and subsequent processing are facilitated, in clinical application, the artificial lens can reduce visual interference such as glare and halo, reduce the risk of secondary surgery, is suitable for long-term implantation of patients with ametropia such as cataract and high myopia, and can provide safer and more durable visual quality guarantee for the patients.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to an artificial lens, its preparation method, and its application. Background Technology

[0002] An intraocular lens (IOL) is a precision medical implant used to replace the eye's natural lens when it becomes cloudy or dysfunctional. It replaces or supplements the refractive function of the natural lens, restoring the eye's ability to focus light onto the retina. Surgically implanted inside the eye, it can correct refractive errors caused by cataracts, high myopia, and other conditions. After IOL implantation, the long-term stability of the patient's visual quality is a key indicator for evaluating its clinical effectiveness. Among these indicators, "flicker performance" is an important parameter for measuring the long-term stability of the IOL.

[0003] Excellent luminescence performance typically refers to a lower and slower degree of microbubbling, cloudiness, or luminescence in the intraocular lens (IOL) after simulated aging (such as accelerated luminescence experiments). IOLs with excellent luminescence performance better maintain long-term clarity and visual quality, specifically in the following aspects: First, maintaining high contrast sensitivity: Over time, the transparency of the lens is fundamental to clear vision. A stable lens can maintain efficient and regular light transmission over a long period, ensuring good contrast sensitivity for patients in different lighting environments (especially at night or in low light), resulting in clearer and more realistic vision. Second, reducing visual disturbances: Light scattering caused by microbubbling or cloudiness is one of the causes of postoperative glare, halos, and other stray light phenomena. Theoretically, lenses with good luminescence performance have a lower probability and severity of these interfering visual symptoms many years after implantation, ensuring greater visual comfort in scenarios such as night driving. Finally, reducing the risk of secondary surgery: In rare cases, if the lens becomes severely cloudy due to material degradation (called "IOL cloudiness"), a risky secondary surgery may be required for replacement. From a materials science perspective, long-term flash stability means a lower risk of long-term turbidity.

[0004] However, the widely used crySof SN60WF intraocular lens (IOL) performs poorly in flash acceleration experiments, exhibiting a high density of microvacuoles after acceleration. These microvacuoles can interfere with patients' visual quality clinically, affecting postoperative visual experience and satisfaction. Therefore, there is an urgent need to develop an IOL with superior flash performance and better long-term stability to address the microvacuole formation problem in existing technologies and improve patients' postoperative visual quality and quality of life. Summary of the Invention

[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, one object of the present invention is to provide an artificial lens.

[0006] The second objective of this invention is to provide a method for preparing such an artificial lens.

[0007] The third objective of this invention is to provide applications for this type of intraocular lens.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides an artificial lens comprising the following raw materials: 2-phenylethyl acrylate, 2-styrene methacrylate, a crosslinking agent, and an initiator.

[0009] In some embodiments of the present invention, the mass ratio of 2-phenylethyl acrylate (PEA) to 2-methacrylic styrene acrylate (PEMA) is 1:(1.8-2.8).

[0010] In some preferred embodiments of the present invention, the mass ratio of 2-phenylethyl acrylate to 2-methacrylic styrene acrylate is 1:(2.1-2.6).

[0011] In some embodiments of the present invention, the amount of the crosslinking agent is 5%-10% of the total mass of the 2-phenylethyl acrylate and 2-methacrylic styrene acrylate.

[0012] In some preferred embodiments of the present invention, the amount of the crosslinking agent is 6%-8% of the total mass of the 2-phenylethyl acrylate and 2-methacrylic styrene acrylate.

[0013] In some embodiments of the present invention, the amount of the initiator is 0.1%-0.5% of the total mass of the 2-phenylethyl acrylate and 2-methacrylate styrene.

[0014] In some preferred embodiments of the present invention, the amount of the initiator is 0.1%-0.3% of the total mass of the 2-phenylethyl acrylate and 2-methacrylate styrene.

[0015] In some embodiments of the present invention, the crosslinking agent is selected from at least one of ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, and 1,4-butanediol dimethacrylate.

[0016] In some preferred embodiments of the present invention, the crosslinking agent is ethylene glycol dimethacrylate (EGDMA).

[0017] In some embodiments of the present invention, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.

[0018] In some preferred embodiments of the present invention, the initiator is azobisisobutyronitrile (AIBN).

[0019] A second aspect of the present invention provides a method for preparing the artificial lens described in the first aspect of the present invention, comprising the following steps: The raw materials are mixed, and the resulting mixture is subjected to deoxygenation and preheating in sequence, followed by a two-stage heating polymerization reaction to obtain the artificial lens.

[0020] In some embodiments of the present invention, the deoxygenation includes purging with nitrogen for 25-35 minutes.

[0021] In some embodiments of the present invention, the preheating temperature is 60-65°C.

[0022] In some embodiments of the present invention, the two-stage heating polymerization reaction includes reacting at 65-75°C for 20-30 hours first, and then reacting at 80-90°C for 0.5-2 hours.

[0023] In some preferred embodiments of the present invention, the two-stage heating polymerization reaction includes reacting at 70-75°C for 20-25 hours first, and then reacting at 80-85°C for 1-2 hours.

[0024] In some embodiments of the present invention, after the two-stage heating polymerization reaction is completed, purification, extraction and drying operations are also included.

[0025] In some embodiments of the present invention, the purification extraction includes ethanol filtration.

[0026] A third aspect of the invention provides the use of the intraocular lens described in the first aspect of the invention in the preparation of a medical device for refractive lens replacement.

[0027] The basic principles of this invention are explained as follows: 1) This invention uses 2-phenylethyl acrylate (PEA) and 2-styrene methacrylate (PEMA) as main monomers. PEA contains a benzene ring, which gives the material a high refractive index. The acrylate structure can give the main chain a certain degree of flexibility, making it easy to process and implant. The α-methyl group of methacrylate in PEMA restricts the movement of chain segments, giving the material a certain degree of rigidity and making it less prone to deformation. At the same time, the benzene ring further increases the refractive index. Ethylene glycol dimethacrylate (EGDMA) is preferred as a crosslinking agent. EGDMA contains two carbon-carbon double bonds, which can connect the linear PEA / PEMA chains during the polymerization process to form a network structure. This structure can effectively prevent the entry of water molecules, thereby effectively suppressing the flash of the material, maintaining the shape and performance stability of the material, and preventing it from being dissolved and melted. 2) PEA and PEMA undergo polymerization in the presence of crosslinking agents and initiators. Initiation stage: The initiator decomposes upon heating, generating free radicals. Since oxygen is a scavenger of free radicals, it consumes the generated free radicals, leading to polymerization failure. Therefore, oxygen is removed before preheating. Chain growth stage: Free radicals open the carbon-carbon double bonds (C=C) of PEA and PEMA, forming new carbon-carbon single bonds and generating new free radical centers, causing the chain to continuously extend. Crosslinking stage: Chain free radicals attack one double bond of the crosslinking agent EGDMA, inserting it into the main chain. The unreacted double bond at the other end of EGDMA can connect to another polymer chain. This bifunctional structure transforms the polymer from a linear structure to a three-dimensional network structure, thus giving the material a fixed shape and certain mechanical strength. This invention employs a two-stage heating process. The first stage controls the reaction rate through a low-temperature, long-time reaction to avoid excessively rapid polymerization, ensuring stable chain growth and forming a uniform polymer network. The second stage increases the temperature to activate residual monomers or incompletely reacted end groups, improving monomer conversion and reducing the leaching of toxic residues in the later stages.

[0028] Compared with the prior art, the beneficial effects of the present invention are: 1) The intraocular lens provided by this invention has a good balance between cross-linking density and material toughness. After accelerated aging, the microvacuole density is significantly reduced compared with existing products (AcrySof IQ SN60WF), effectively suppressing the flicker phenomenon and better maintaining long-term clarity and visual quality. The intraocular lens has high thermal stability, with an initial decomposition temperature of up to 295℃, which facilitates high-temperature sterilization and subsequent processing. In clinical applications, the intraocular lens can reduce visual interference such as glare and halo, reduce the risk of secondary surgery, and is suitable for long-term implantation in patients with cataracts and refractive errors such as high myopia, providing patients with safer and more durable visual quality assurance. 2) The method for preparing artificial lenses provided by this invention adopts a two-stage heating polymerization reaction. The low-temperature, long-time reaction in the first stage ensures stable chain growth and uniform network, improving anti-sparkling performance. The high-temperature, short-time reaction in the second stage improves monomer conversion rate and reduces residues. Through purification and extraction methods such as ethanol filtration, unreacted monomers, oligomers, residual initiator fragments, and other toxic and harmful small molecules can be replaced to achieve medical-grade purification and ensure safety after implantation into the human body. Attached Figure Description

[0029] Figure 1 Fourier transform infrared spectra of PEA, PEMA, and the intraocular lenses in Examples 1-3; Figure 2 Thermogravimetric analysis curves of intraocular lenses with different crosslinking agent contents in Examples 1-3; Figure 3Macroscopic photographs of intraocular lenses with different crosslinking agent contents in Examples 1-3; Figure 4 These are macroscopic photographs of intraocular lenses with different crosslinking agent contents from Examples 1-3 after being subjected to flash acceleration; Figure 5 Macroscopic photographs of the intraocular lenses in Examples 4(a) and 5(b); Figure 6 These are photographs of intraocular lenses with different crosslinking agent contents from Examples 1-3 under a 100x microscope; Figure 7 These are photographs of intraocular lenses with different crosslinking agent contents from Examples 1-3 under a 100x microscope after being subjected to flash acceleration; Figure 8 These are photographs of the intraocular lenses in Example 3(a) and Comparative Example 1(b) after being subjected to flash acceleration under a 100x microscope. Detailed Implementation

[0030] The present invention will be further described in detail below through specific embodiments. Unless otherwise specified, the raw materials, reagents, or apparatus used in the embodiments and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the test or experimental methods are conventional methods in the art.

[0031] Note: 2-Phenylacetyl acrylate and 2-Styrene methacrylate used in the examples were purchased from Anaiji Chemical; ethylene glycol dimethacrylate and azobisisobutyronitrile were purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0032] Example 1 This embodiment prepares an intraocular lens containing 5 wt% crosslinking agent, and the steps are as follows: 0.3 g of 2-phenylethyl acrylate, 0.7 g of 2-methacrylate, 0.05 g of ethylene glycol dimethacrylate, and 2 mg of azobisisobutyronitrile were mixed under stirring at room temperature. The resulting mixture was purged with nitrogen for 30 min to remove oxygen. After preheating at 60 °C, it was rapidly injected into a cylindrical glass mold. The mold was sealed and placed in an oven. The reaction was carried out at 70 °C for 24 h and then at 85 °C for 1 h to complete the polymerization of the remaining monomers. After the reaction was completed, the mixture was demolded, filtered with ethanol, and vacuum dried to obtain an artificial lens.

[0033] Example 2 This embodiment prepares an intraocular lens containing 7 wt% crosslinking agent, and the steps are as follows: 0.3 g of 2-phenylethyl acrylate, 0.7 g of 2-methacrylate, 0.07 g of ethylene glycol dimethacrylate, and 2 mg of azobisisobutyronitrile were mixed under stirring at room temperature. The resulting mixture was purged with nitrogen for 30 min to remove oxygen. After preheating at 60 °C, the mixture was rapidly injected into a cylindrical glass mold. The mold was sealed and placed in an oven. The reaction was carried out at 70 °C for 24 h, followed by a reaction at 85 °C for 1 h to complete the polymerization of the remaining monomers. After the reaction was completed, the mixture was demolded, filtered with ethanol, and vacuum dried to obtain an artificial lens.

[0034] Example 3 This embodiment prepares an artificial lens containing 10 wt% crosslinking agent, and the steps are as follows: 0.3 g of 2-phenylethyl acrylate, 0.7 g of 2-methacrylate, 0.10 g of ethylene glycol dimethacrylate, and 2 mg of azobisisobutyronitrile were mixed under stirring at room temperature. The resulting mixture was purged with nitrogen for 30 min to remove oxygen. After preheating at 60 °C, the mixture was rapidly injected into a cylindrical glass mold. The mold was sealed and placed in an oven. The reaction was carried out at 70 °C for 24 h and then at 85 °C for 1 h to complete the polymerization of the remaining monomers. After the reaction was completed, the mixture was demolded, filtered with ethanol, and vacuum dried to obtain an artificial lens.

[0035] Example 4 This embodiment modifies the ratio of the two monomers to prepare an artificial lens, and the steps are as follows: 0.7 g of 2-phenylethyl acrylate, 0.3 g of 2-methacrylate, 0.07 g of ethylene glycol dimethacrylate, and 2 mg of azobisisobutyronitrile were mixed under stirring at room temperature. The resulting mixture was purged with nitrogen for 30 min to remove oxygen. After preheating at 60 °C, the mixture was rapidly injected into a cylindrical glass mold. The mold was sealed and placed in an oven. The reaction was carried out at 70 °C for 24 h and then at 85 °C for 1 h to complete the polymerization of the remaining monomers. After the reaction was completed, the mixture was demolded, filtered with ethanol, and vacuum dried to obtain an artificial lens.

[0036] Example 5 This embodiment modifies the ratio of the two monomers to prepare an artificial lens, and the steps are as follows: 0.5 g of 2-phenylethyl acrylate, 0.5 g of 2-styrene methacrylate, 0.07 g of ethylene glycol dimethacrylate, and 2 mg of azobisisobutyronitrile were mixed under stirring at room temperature. The resulting mixture was purged with nitrogen for 30 min to remove oxygen. After preheating at 60 °C, the mixture was rapidly injected into a cylindrical glass mold. The mold was sealed and placed in an oven. The reaction was carried out at 70 °C for 24 h, followed by a reaction at 85 °C for 1 h to complete the polymerization of the remaining monomers. After the reaction was completed, the mixture was demolded, filtered with ethanol, and vacuum dried to obtain an artificial lens.

[0037] Comparative Example 1 This comparative example uses a commercially available intraocular lens (AcrySof IQ) as a control, with specifications SN60WF.

[0038] Performance testing 1. The polymer monomers 2-phenylethyl acrylate (PEA) and 2-styrene methacrylate (PEMA), as well as the intraocular lenses prepared in Examples 1-3, were measured using a PerkinElmer Spectrum Two infrared spectrometer in the range of 400-4000 cm⁻¹. -1 Infrared absorption peaks within the wavelength range: Figure 1 The Fourier transform infrared spectra of PEA, PEMA, and the intraocular lenses in Examples 1-3 are provided by [the relevant source]. Figure 1 It can be seen that, compared to PEA and PEMA, the intraocular lenses in Examples 1-3 have a lower octane rating of 812 cm. -1 The characteristic peak disappears at 1620 cm⁻¹. -1 The characteristic peak at 812 cm⁻¹ weakened significantly. -1 The characteristic peak at 1620 cm⁻¹ usually corresponds to the out-of-plane bending vibration of CH in olefins. Both PEA and PEMA contain terminal olefin structures, and the disappearance of this characteristic peak directly proves the successful occurrence of the polymerization reaction. -1 The characteristic peak corresponds to the stretching vibration of the carbon-carbon double bond. The significant weakening of this characteristic peak also proves the consumption of the double bond. The Fourier transform infrared spectroscopy characterization results confirm that the monomer synthesized a copolymer through chemical bonds, that is, the artificial lens was successfully prepared.

[0039] 2. Using Netzsch TG 209 F3 Tarsus ® Thermogravimetric analysis was used to determine the thermal decomposition properties of the intraocular lenses prepared in Examples 1-3. The samples were heated from room temperature to 500°C at a rate of 20°C / min in a nitrogen atmosphere. Figure 2 Thermogravimetric analysis curves of intraocular lenses with different crosslinking agent contents in Examples 1-3 are provided by... Figure 2 It can be seen that the initial decomposition temperature (T95%) of the intraocular lenses in Examples 1-3 were 280℃, 287℃ and 295℃, respectively, and the final decomposition residues were 3.93%, 3.92% and 3.82%, respectively. This indicates that as the content of the crosslinking agent ethylene glycol dimethacrylate increases, the crosslinking density of the material is higher, the thermal stability is better, and it is easier to process in subsequent steps.

[0040] 3. Photographs were taken of the intraocular lenses obtained in Examples 1-5 using a camera, and a flash acceleration experiment was performed on the intraocular lenses obtained in Examples 1-3. Each intraocular lens sample was heated in distilled water at 45±1℃ for 24 hours and then rapidly moved to a water bath at 37±1℃. After 2.5 hours, the sample was photographed again, and the light transmittance of the intraocular lenses before and after the experiment was compared. Figure 3 These are macroscopic photographs of intraocular lenses with different crosslinking agent contents from Examples 1-3. Figure 3 In the examples (a), (b), and (c), the intraocular lenses correspond to those in Examples 1-3, with crosslinking agent contents of 5 wt%, 6 wt%, and 10 wt%, respectively. Figure 3 It can be seen that all three types of artificial lenses containing different proportions of crosslinking agent can form highly transparent samples with regular shape and uniform structure. However, the artificial lens containing 10wt% crosslinking agent has high crystal hardness and brittleness due to the excessive crosslinking agent content, which is not conducive to processing.

[0041] Figure 4 These are macroscopic photographs of intraocular lenses with different crosslinking agent contents from Examples 1-3 after being subjected to flash acceleration. Figure 4 (a), (b), and (c) in the figures correspond to the intraocular lenses in Examples 1-3, respectively. Figure 4 It can be seen that after the flash acceleration experiment, the transparency of the intraocular lens containing 5 wt% crosslinking agent in Example 1 decreased significantly, while the intraocular lenses containing 7 wt% and 10 wt% crosslinking agent in Examples 2 and 3 could still maintain high transparency. Considering the hardness, brittleness and light transmission performance of the lens, the optimal amount of crosslinking agent is 6%-8% of the total mass of PEA and PEMA.

[0042] Figure 5 Macroscopic photographs of the intraocular lenses used in Examples 4(a) and 5(b). Figure 5 It is evident that after altering the ratio of monomers PEA and PEMA in Examples 4 and 5, only fragmented lenses were obtained, making effective shaping difficult. Therefore, the optimal ratio (mass ratio) of monomers PEA and PEMA is 1:(1.8-2.8).

[0043] 4. The glitter performance of the intraocular lenses in Examples 1-3 and Comparative Example 1 was analyzed using a Nikon Eclipse 50i POL polarizing microscope. In the glitter acceleration experiment, each intraocular lens sample was heated in distilled water at 45±1℃ for 24 hours and then rapidly moved to a water bath at 37±1℃ for 2.5 hours. Optical microscopy was then performed to observe the density and size of microbubbles at the center of the intraocular lens. Figure 6These are photographs of intraocular lenses with different crosslinking agent contents from Examples 1-3 under a 100x microscope. Figure 6 (a), (b), and (c) in the figures correspond to the intraocular lenses in Examples 1-3, respectively. Figure 6 It can be seen that the three intraocular lenses containing different proportions of crosslinking agents all exhibited a uniform microstructure, a dense texture, and no microbubbles, showing good lens characteristics.

[0044] Figure 7 These are photographs of intraocular lenses with different crosslinking agent contents from Examples 1-3 under a 100x microscope after being subjected to flash acceleration. Figure 7 (a), (b), and (c) in the figures correspond to the intraocular lenses in Examples 1-3, respectively. Figure 7 It can be seen that, in Example 1, the intraocular lens containing 5 wt% crosslinking agent exhibited relatively obvious and uniform microbubbles throughout the entire microscope field of view after the flash acceleration experiment. This indicates that the intraocular lens with 5 wt% crosslinking agent has poor flash performance. Meanwhile, with the increase of the crosslinking agent ethylene glycol dimethacrylate content, the microbubble density of the intraocular lenses in Examples 2 and 3 decreased significantly under the microscope, indicating a significant improvement in the flash performance of the material. However, excessive crosslinking agent content leads to high crystal hardness and brittleness, which is detrimental to processing. Therefore, the optimal amount of crosslinking agent is approximately 7% of the total mass of PEA and PEMA.

[0045] Figure 8 These are photographs of the intraocular lenses in Example 3(a) and Comparative Example 1(b) after being subjected to flash acceleration under a 100x microscope. Figure 8 It is known that, under the same experimental conditions, the intraocular lens prepared in Example 3 produces fewer microbubbles after flash acceleration, indicating that its flash performance is superior. In the complex biological environment inside the eye, its structure is more stable and less prone to the formation of tiny cavitations or turbidity over time. When used as a refractive lens replacement medical device for ophthalmic diseases such as cataracts, it is more conducive to ensuring that the visual quality of patients does not decline due to changes in the lens itself many years after surgery. Therefore, the intraocular lens provided by this invention has flash performance superior to the existing commercially available product AcrySof IQ SN60WF and can better meet the needs of clinical applications.

Claims

1. An artificial lens, characterized in that, It is prepared from the following raw materials: 2-phenylethyl acrylate, 2-styrene methacrylate, crosslinking agent, and initiator; wherein, The crosslinking agent is selected from ethylene glycol dimethacrylate; the initiator is selected from azobisisobutyronitrile. The mass ratio of 2-phenylethyl acrylate to 2-methacrylic styrene is 1:(2.1-2.6); The amount of the crosslinking agent is 6%-8% of the total mass of the 2-phenylethyl acrylate and 2-methacrylic styrene acrylate; The amount of the initiator is 0.1%-0.5% of the total mass of the 2-phenylethyl acrylate and 2-methacrylic styrene acrylate; The method for preparing the artificial lens includes the following steps: The raw materials are mixed, and the resulting mixture is subjected to deoxygenation and preheating in sequence, followed by a two-stage heating polymerization reaction to obtain the artificial lens. The preheating temperature is 60-65℃; the two-stage heating polymerization reaction is first reacted at 70-75℃ for 20-25 hours, and then reacted at 80-85℃ for 1-2 hours.

2. The use of the intraocular lens of claim 1 in the preparation of a medical device for refractive lens replacement.

Citation Information

Patent Citations

  • Process for producing a hydrophobic acrylic polymer material for an ophthalmic device

    WO2015070981A1